Patterns of variation in sociomusical identity of school-goers in a condition of social vulnerability and musical gaps in their education - Angel-Alvarado, Rolando; Casas-Mas, Amalia; López-Íñiguez, Guadalupe; Johnson, Lauren (Taylor & Francis, 2022)
Sociomusical identity pursues integrative goals, as it establishes bridges between musical identities from a perspective based on transculturation and post-ethnicity. The current study aims to observe the influence of social groups in the construction of sociomusical identity, using a simple random sample comprised of 417 students who attend Chilean schools classified in a condition of social vulnerability. The chosen nonexperimental quantitative method is survey research, as two scales were applied to measure musical activities in different social groups. Results indicated that the musical performance variable explains social differences in the distribution of sociomusical capital because, just as Western culture fosters the musician-listener dualism, it also causes gaps in sociomusical identity. In conclusion, differentiation points in sociomusical identity are linked to social matters concerning musical performance, as school-goers’ musical practice is not encouraged inside nor outside of schools.
Keywords: musiikki; musiikkikasvatus; identiteetti; ammatti-identiteetti; oppiminen